Some Variants of Wayment's Mean Value Theorem for Integrals - Lozada-Cruz, German (2025)
This note deals with some variants of Wayment’s Mean Value Theorem for integrals. Our approach is rather elementary and does not use advanced techniques from analysis. The simple auxiliary functions were used to prove the results.